Blackstone's statutes on criminal law 2018-2019 - Dyson, Matthew
Celebrating over 30 years as the market-leading series, Blackstone's Statutes have an unrivalled tradition of trust and quality. With a rock-solid reputation for accuracy, reliability, and authority, they remain first-choice for students and lecturers, providing a careful selection of all the up-to-date legislation needed for exams and course use.
Keywords: Criminal law -- England; Criminal law -- Wales